The effects of UV degradation on the physical, thermal, and morphological properties of industrial nylon 66 conveyor belt fabrics. (August 2020) - Moezzi, Meysam; Yekrang, Javad; Ghane, Mohammad; Hatami, Mehdi
In this study, nylon 66 industrial fabrics (used in the conveyor belts) were exposed artificially to the accelerated ultraviolet rays and the degradation mechanism was evaluated using spectral, thermal, and morphological analyses. The fabric samples were exposed to six different exposure times in a UV chamber and tensile tests were carried out in the main and bias (45°) directions. The results showed that the shear modulus was reduced in the early stages covering 4 h of the UV radiation because of the linkages breakage and the increase in the amorphous regions. However, after this early stage, the shear modulus started to increase. The Fourier transform infrared spectroscopy (FTIR), scanning electron microscope (SEM) analysis, and X-ray photoelectron spectroscopy (XPS) study were also performed to evaluate the surface morphology and the degradation mechanism of the nylon 66 fibers after UV illumination. The results also revealed that the formation of new links by free radicals caused the change in the bond wavelengths. Furthermore, it was found that there was an interesting mechanism for the UV degradation of nylon 66 fabrics at different exposure times, as confirmed by the results obtained regarding the mechanical properties of the samples. The results of this study can be, therefore, helpful for the industrial application of nylon 66 woven conveyor belts exposed to solar UV radiation.